(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
This study aimed to determine the prevalence of dermatophytosis infections among patients attending National obstetrics fistula center Babbar-ruga hospital, Katsina state. A total number of 100 patients were diagnosed, (40/100) were males and 60% (60/100) were females, giving a gender ratio of 3:2 (males: females), 40% of the participants were of the age range 10-29 years and 60% of age from 14-21 years respectively. Out of 60 cases, a total of 53 dermatophytes were isolated belonging to the genera Trichophyton and Microsporum. The most frequently isolated dermatophytes were Trichophyton mentagrophyte (26.41% 14/53), followed by Microsporum audouinii (22.64% 12/53), Trichophyton rubrum (15.09% 8/53), Trichophyton schoenleinii (7.547% 4/53), Microsporum gypseum (5.660% 3/53) and the least were Microsporum canis (9.433% 5/53) and Trichophyton tonsurans (9.433% 5/53), Trichophyton verrucosum (3.77% 2/53). Although 38 cases (63.33%) had single infections with dermatophytes, mixed infections with 2-4 dermatophytes of the genera Microsporum and Trichophyton were observed in 15 cases (36.67%). 67% (10/15) of the mixed infections were with Microsporum and Trichophyton species, 20% (3/15) were with Microsporum species alone, and 13.3 %( 2/15) were with Trichophyton species alone. This study indicates an outstanding prevalence of dermatophytosis infection among patients who shared combs and scarves and who owned pets; this suggests a thriving animal-human transmission route of dermatophytes and the potentiality of the fomites. The research proposes intensive health promotion and education interventions to promote hygiene practices among patients.